FORMULATION AND EVALUATION OF HERBAL ANTACID CHOCOLATE FOR THE MANAGEMENT OF ACIDITY USING NATURAL INGREDIENTS - Karishma Rajendra Jathar; Viraj Abasaheb Awatade; Gorakshnath Balu Garje; Sakshi Santosh Chakane; Smita Vishnu Borude; Vishal Bhivraj Kaygude; Rushikesh Haribhau Ambekar; Omkar Umesh Jadhav; Vaishnavi Sanjay Sake; Dr. Amol Navnath Khedkar (The Bioscan, 2026)
Hyperacidity is a common gastrointestinal disorder associated with excessive gastric acid secretion, causing symptoms such as heartburn, acid reflux, and indigestion. The present study aimed to formulate and evaluate a herbal antacid chocolate containing medicinal plant extracts with antacid and gastroprotective properties. The formulation was prepared using herbal extracts along with cocoa butter, cocoa powder, milk powder, and sugar. The prepared chocolate was evaluated for physicochemical properties, organoleptic characteristics, stability, and antacid activity. The formulation exhibited satisfactory physical characteristics, good stability, pleasant taste, and significant acid-neutralizing activity. The results indicate that herbal antacid chocolate may serve as a convenient, palatable, and effective alternative to conventional antacid preparations for the management of hyperacidity